Theoretical Justification of the Principle of Somatic Education of Girl-Students of Higher Educational Establishments by Tomas Hanna’s Method - Maksymova, Kateryna (Pedagogical Discourse, 2017)
The article presents the theoretical justification of somatic education of girl-students of higher educational establishments by Tomas Hanna’s method. The deterioration of girl-students’ somatic health of higher educational establishments of Ukraine in recent years is pointed out. The modern process of modernization of higher education requires the improvement of the quality of training of specialists in all spheres. The effective way to improve the somatic health by using principle of somatic education of girl-students during physical education classes is defined. The peculiarity of the principle of somatic education through the movement one’s own body which leads to the improving somatic health and physical fitness, removal of chronic tension, the development of the ability to control muscles as well as to understand the students themselves as a responsible person for their own resources of the body are indicated. Health problem of modern youth as a major problem in the field of pedagogy, physical education and medicine is indicated nowadays. The search of effective ways of influencing, strengthening and improving especially the 1st year girl-students’ health is relevant. The problem of correction of somatic health remains relevant and requires its solution to modernize the system of physical education as a component of the educational process in the system of higher education. The study and prevention of the somatic health of modern youth should be ensured through the application of the synergistic approach. This involves qualitative combination of phenomena, relationships, their interactions and increasing the effectiveness of the training process. So, the principle of somatic education of the 1st year girl-students is formed awareness through the movement of their own body, removal of chronic stress, correction of somatic health, restoration of neuromuscular connections and memory, development of sensuality and ability to control muscles, breathing and movements, understanding of students as an active and responsible person for their own resources of the body which can be used during various health-improving exercises.